Spacing and induction: Application to exemplars presented as auditory and visual text - Norehan, Zulkiply; John, McLean; Jennifer S., Burt; Debra, Bath (Elsevier, 2012)
It is an established finding that spacing repetitions generally facilitates memory for the repeated events. However, the effect of spacing of exemplars on inductive learning is not really known. Two experiments using textual material were conducted to investigate the effect of spacing on induction. Experiment 1 and 2 extended the generality of recently observed spacing benefits to texts, regardless of whether they were visually or aurally presented. Interestingly, participants in both experiments judged massing to be more effective than spacing though their performance showed the opposite. Possible explanations for the superiority of the spaced condition over the massed condition in inductive learning, practical implications of the present study and suggestions for future research are discussed.